2020
DOI: 10.1108/bfj-08-2019-0582
|View full text |Cite
|
Sign up to set email alerts
|

Brexit-related food issues in the UK print media: setting the agenda for post-Brexit food policy

Abstract: PurposeThe purpose of this paper is to explore how Brexit-related food issues are being presented in the UK print media.Design/methodology/approachUsing the news database Nexis UK, relevant articles were identified based on key search terms, “Brexit” and “Food” or “Farm!” or “Agriculture!”. The search criteria were set to include articles with three or more mentions of these terms. The search period was 6 April to 5 July 2018.FindingsThe quality newspaper genre, and remain-supporting newspaper, The Guardian, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…Media articles cited information from government sources (50% of articles) more frequently than information attributed to food sector representatives (42% of articles), academics and other experts (22%) or opposition party politicians (6% of articles). While previous studies have criticised the media’s disproportionate representation of politicians initially involved in shaping the Brexit campaign [ 26 , 27 ], it is well recognised that politicians use the media as a tool for communicating with the public and a way to influence public opinion [ 28 ], and these findings support previous research which also found political voices to feature more prominently than other stakeholder groups [ 7 ].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Media articles cited information from government sources (50% of articles) more frequently than information attributed to food sector representatives (42% of articles), academics and other experts (22%) or opposition party politicians (6% of articles). While previous studies have criticised the media’s disproportionate representation of politicians initially involved in shaping the Brexit campaign [ 26 , 27 ], it is well recognised that politicians use the media as a tool for communicating with the public and a way to influence public opinion [ 28 ], and these findings support previous research which also found political voices to feature more prominently than other stakeholder groups [ 7 ].…”
Section: Discussionsupporting
confidence: 74%
“…For the general population, an important source of information on food supply chain disruption and food shortages was the mass media [ 7 ]. The nature of information conveyed through the media, including what gets reported, can have a powerful effect on public knowledge, attitudes and behaviours [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is supported by a previous media analysis of Brexit-related food issues, which identified political voices to feature more prominently than other stakeholder groups, highlighting the significant potential for this group to influence public opinion. 9 Warnings from the food sector were generally supported by what is known about the UK food system. In 2016 / 2017, the food sector warned of a shortage of migrant farm workers from the EU in the event of a no-deal Brexit, with approximately 75,000 seasonal workers entering the UK each year.…”
Section: Main Findings Of This Studymentioning
confidence: 99%
“…8 Previous research exploring how the media report on food, farming and agriculture, in the context of Brexit, found media outlets to select and promote issues that reinforce their own political agenda. 9 This research, however, only focused on a three-month period in 2018 and did not consider the role of the media in promoting reassurance or anxiety on the issue of food shortages. This is of particular importance given the vulnerabilities in the UK food system highlighted during the Covid-19 pandemic 10 and the increased likelihood of a no-deal Brexit.…”
Section: Introductionmentioning
confidence: 99%